Anglicism: an active word-formation mechanism in Spanish - Gerding-Salas, Constanza; Fuentes, Mary; Gómez, Lilian; Kotz, Gabriela (Colombian Applied Linguistics Journal, 2014)
The adoption of the American neoliberal paradigm has resulted in significant social changes worldwide. Its effects are evident in different fields including language use. Thus, the influence of the English language and American culture on other languages is of interest tolinguists, translators, and SL teachers. This study aimed at identifying the presence of Anglicisms in the press in order to describe them, determine their frequency and patterns of use, and infer the causes of their incorporation in Spanish as well as its implications for SL teaching. Anglicisms were collected by the Antena Chilena de Neología between 2006 and 2012 and then analyzed according to formal characteristics and contextual domains. Results showed that Anglicisms have a strong presence in today’s press in economics, computer science, sports, and culture, and that speakers adopt rather than adapt them. Four factors may explain the introduction of Anglicisms to Spanish: lexical gaps, social prestige, linguistic economy, and user preference. It was concluded that the English language and American culture have a significant presence in the press through Anglicisms, which needs to be taken into account in ESL teaching and translator training.